Local Wisdom Gaming for Understanding and Interesting (Lossing Saddler) in Learning Magnet in Lentera Elementary School - Syntyche Riyani; Wahyu Hari Kristiyanto; Adi Winanto (Postgraduate, University of Mataram, 2025)
This study was motivated by students' low understanding of IPAS (Natural and Social Sciences) material and difficulties during group discussions. Most students only enjoyed the practical activities and felt burdened by the notes that had to be memorised. Based on interviews with 50 students, it was found that confusion and the burden of memorisation were the main obstacles. To overcome this, the researcher developed the ‘LOSSING SADDLER’ (Local wisdom gaming for understanding and interesting learning combine with guessing word) method to improve the understanding of magnetic concepts and interest in learning IPAS in Phase C students. The research subjects included Grade V students of SD Kristen Lentera Ambarawa as the experimental class and students from six learning community primary schools in Semarang Regency as the comparison. Data were collected through unstructured interviews, documentation, tests and observations, and analysed descriptively quantitatively. This study aims to determine the effect of the ‘LOSSING SADDLER’ method on the understanding of magnetic material and the increase in student learning motivation. The expected results show that this method is able to increase students' understanding and interest in IPAS learning through a fun and meaningful approach.